Performance Optimization of Hg1-xCdxTe Photovoltaic Detectors Under Strong Illumination Considering Temperature and Wavelength Dependencies - Jiahui Chen; Wangyong Chen; Linlin Cai; Pengling Yang; Dahui Wang; Manling Shen; Xiangyang Li; Hui Qiao (IEEE Photonics Journal, 2024)
Currently, HgCdTe detectors are advancing towards very long wavelengths and room temperature operation. However, as operating temperatures and illumination intensity increase, the performance of these detectors deteriorates, evidenced by increased dark current, reduced responsivity and detectivity, and enhanced saturation effects. These limitations significantly hinder the application of detectors for strong illumination scenarios at room temperature. In this study, we utilize compositional gradients and array electrode designs to make better trade-offs among dark current, responsivity, and saturation characteristics of HgCdTe photovoltaic detectors under mid-wave and long-wave infrared conditions. We elucidate the underlying mechanisms from the perspectives of the responsive region and the non-photosensitive area, as well as carrier motion and recombination processes. The results indicate that increasing compositional gradients are beneficial for reducing dark current, while decreasing compositional gradients are advantageous for improving responsivity. Moreover, detectors with array electrodes design achieve a peak responsivity of 1.5 A/W under 200 W/cm2 (∼1.8 mW) at room temperature, which is three times higher than the pre-optimized structure. Additionally, the peak detectivity increased by more than 20%. These research findings provide guidance for the design of future HgCdTe detectors operating under strong injection levels and at various temperatures.